Pengembangan E-Lkpd Berbasis Aplikasi Socrative untuk Pembelajaran Menyimak Teks Cerita Fabel pada Siswa Kelas VII SMP Negeri 8 Palembang - Muhammad Alhamd; Ansori Ansori (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to create an E-LKPD product supported by the Socrative application for teaching listening to fable texts in class VII of SMP Negeri 8 Palembang. The purposes of this study are to describe the analysis of teachers and students needs for the development of socrative-based E-LKPD, and to produce the design and development of Socrative based E-LKPD for learning fable texts in class VII. The type of research used was development research with the ADDIE model, which consists if five stages: analysis, design, development, implementation, and evaluation. The data collection techniques used were observation, interviews, validation sheets, questionnaires, and written tests. The result of the language expert validation obtained a percentage of 78% in the acceptable category. The material expert validation obtained. The material expert validation it with 89%, which is very feasible. The student’s questionnaire showed 98%, which is very good. The N-Gain score was 0.63, which is moderate. So, it can be concluded that the E LKPD product using the Socrative app is suitable for use in learning activities.